Fetal pleural effusions in west of Scotland – causes, seasonal trends and outcomes. (18th April 2012) - Wu, P; Cameron, AD; Chen, M; Brennand, J; Ledingham, MA; Gibson, JL
Abstract : Fifty-five fetuses with pleural effusion were seen in our unit over last 9 years. Twenty-six cases (47%) did not have associated anomaly and were of uncertain aetiology. Twelve (22%) had associated structural anomalies without evidence of abnormal karyotypes. Cardiac anomalies were most common, while abnormalities in brain, kidneys and bones were also seen. Twelve fetuses had abnormal karyotypes (Trisomy 21 and Turner's syndrome), 2 had parvovirus B19 and 1 had listeria. One fetus had supraventricular tachycardia and another had cardiac rhabdomyomas. There appears to be some seasonal trend for pleural effusions in those uncertain aetiology ( n =26). They presented most frequently in November, October and July. Proven parvovirus cases ( n =2) presented in June and October. Overall, 15/55 (27%) had termination of pregnancy: 5 had hydrops and 10 had associated anomalies. Four patients (7%) were delivered shortly after presentation whilst 21 (38%) had conservative sonographic surveillance. Three IUDs occurred in this group, 2 due to worsening hydrops or rhabdomyomas at 28 weeks and 1 was unexplained at 35 weeks despite postmortem examination. Eight patients (15%) were lost to follow-up. Fifteen cases underwent fetal therapy i.e. pleuro-amniotic shunt, pleural tap, intrauterine transfusion (IUT) or maternal flecainide. Of these, 2 losses occurred post IUT and the remainder had live births or were discharged to referring hospitals for follow-up. We conclude that in the absence of karyotypic or structural anomalies, fetal pleural effusion can have good outcomes with live births as in 36% (20/55) of our cohort.